The mediating effect of Leaders idealized influence on the relationship between leaders emotional intelligence and intention to perform among academics in Malaysian Research Universities: gender as a moderator - Gopalan Raman (Tanjong Malim, 2020)
The mediating effect of Leaders idealized influence on the relationship between leaders emotional intelligence and intention to perform among academics in Malaysian Research Universities: gender as a moderator by Gopalan Raman